Methodical approaches to the production of technical documentation on land management regarding the establishment of the boundaries of a portion of the land subject to the right of sublease, servitude - J. M. Dorosh (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ, 2015)
Done scientific justification and proposed methodological approaches to the production of technical documentation on land management on establishing the boundaries of the land covered by the right to sublease, easement. The purpose of making this type of documentation is setting limits and making the State Land Cadastre of information on land covered by the right to sublease, easement